Results of a randomized controlled phase III trial: efficacy of polyphenol-containing cystus® tea mouthwash solution for the reduction of mucositis in head and neck cancer patients undergoing external beam radiotherapy - Ebert, Nadja; Kensche, Anna; Löck, Steffen; Hadiwikarta, Wahyu Wijaya; Hänsch, Anna; Dörr, Wolfgang; Krause, Mechthild; Hannig, Christian; Baumann, Michael (Strahlentherapie und Onkologie, 2021)
To determine the effect of Cystus® tea (Naturprodukte Dr. Pandalis GmbH & Co. KG) as mouthwash compared to sage tea on oral mucositis in patients undergoing radio(chemo)therapy for head and neck cancer.